APPLICATION OF DIFFUSION EQUATION FOR SINGLE PHASE TO DETERMINE SOME PHYSICAL PROPERTIES OF RESERVOIR - (NIM: 20214035), HARDIYANTO
Pressure transient of oil in reservoir can be obtained from the solution diffusion equation. The solution of this equation requires two boundary conditions in space and time. Solution is obtained using the Laplace transform, and then used in the pressure drop in a flow test (Pressure Drawdown Test) and Pressure buildup Test. The curve plot of the solution is used to predict reservoir parameters such as permeability, skin faktor and pressure drop at “skin” radius. The data were obtained from wells X and CMG-IMEX simulator. The well on simulator was given some treatment as well hydraulic fractured and varied production rate.